PATAHAN AKTIF DAN KEGEMPAAN DAERAH PLTA CIRATA - SAGULING DAN SEKITARNYA - Soehaimi, Asdani (Pusat Survei Geologi, 2010)
Electric Hydro Power of Cirata (PLTA) and Saguling are located at the active thrust fault of Citarum – Cisomang (1) and Saguling (2). The gravity modelling on the north – south direction, shows these structures geology as the bounderies of the structural basin of Cirata and Saguling which are filled by Young Volcanic Deposites. Microearthquakes at the Saguling (I), Cirata (II) and Pasir Cabe (III), have the depth of < 10 Km and shown the thrust, strike slip and normal fault focalmechanisms. The maximum magnitude calculated which was based on the vertical displacement (dip slip) of two main revers fault above are 7 Ms with return period of 80 years.Keywords: active fault, maximum magnitude, return period, Cirata